Role of Social Media in Promotion of Small Business Enterprises: Exploring Strategies for Effective Marketing through Social Media (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Today, we are in 21st century and people do not find time to come & interact with each other. Social media helps in connecting themselves with social networking sites through which now people can stay far and yet remain connected. Apart from this media like Facebook create a loyal connection between product and individual which leads to large advertising opportunities. Similarly, other social media like Blogs create a platform to post comment on any event which needs to be publicized also can be utilized as a promotional technique for customer’s adoption as well as for promotions. Now users are acquiring followers & subscribers and directing them to your social networking page. These media has a competitive edge over other popular public media like Television because there is a time gap between social event occurrence and the time it is being broadcasted. This research paper emphasizes on the strategies which can take this viral marketing mode beyond the normal social media at present. As a result it can also help in building your community strong enough to make your marketing effective & initiative buying.